Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Nguyễn Như

Cần gấp ạ !

Akai Haruma
4 tháng 9 2021 lúc 9:07

Lời giải:

a. 

$A=x^2+6x+9+(x^2-9)-2(x^2-2x-8)$

$=10x+16=10.\frac{-1}{2}+16=-5+16=11$

b.

$B=9x^2+24x+16-(x^2-16)-10x$

$=8x^2+14x+32=8(\frac{-1}{10})^2+14.\frac{-1}{10}+32$

$=\frac{767}{25}$

c.

$C=(x^2+2x+1)-(4x^2-4x+1)+3(x^2-4)$
$=6x-12=6-12=-6$

d.

$D=(x^2-9)+(x^2-4x+4)-(2x^2-8x)$

$=4x-5=4(-1)-5=-9$

 


Các câu hỏi tương tự
Cheer Bomb Đéo Cheer Búa
Xem chi tiết
Ha Thu
Xem chi tiết
Vy trần
Xem chi tiết
Lê Phương Anh
Xem chi tiết
🌼K.L🌼
Xem chi tiết
Như Nguyễn
Xem chi tiết
Phạm Băng
Xem chi tiết
Garcello
Xem chi tiết
Bủh Bủh Dảk Dảk Lmao
Xem chi tiết
Manie Kim
Xem chi tiết